2014
DOI: 10.1007/s10903-014-0091-y
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Cancer Screening by Citizenship and Health Insurance, 2000–2010

Abstract: While early detection through screenings for breast, cervical, and colorectal cancer is essential in improving cancer survival, it is not evenly utilized across class, race, ethnicity, or nativity. Given that utilization of early detection through screenings is not evenly distributed, immigrants who have much lower rates of health insurance coverage are at a disadvantage. We use National Health Interview Survey data linked with the Medical Expenditures Panel Survey to examine the trend in screening rates for b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 26 publications
(24 reference statements)
1
23
0
Order By: Relevance
“…The findings from this study also suggest that Bhutanese-Nepali women have low rates of cervical cancer screening. Low screening rates among our study population are similar to that of Haworth et al (2014) and other studies conducted with refugee and immigrant women [12,14,29]. Perceived barriers to screening among study participants were also similar to those of Asian immigrant women and included barriers such as shyness, fear of having a Pap smear, and experiencing pain or discomfort from having the Pap smear [30,31].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The findings from this study also suggest that Bhutanese-Nepali women have low rates of cervical cancer screening. Low screening rates among our study population are similar to that of Haworth et al (2014) and other studies conducted with refugee and immigrant women [12,14,29]. Perceived barriers to screening among study participants were also similar to those of Asian immigrant women and included barriers such as shyness, fear of having a Pap smear, and experiencing pain or discomfort from having the Pap smear [30,31].…”
Section: Discussionsupporting
confidence: 75%
“…Despite solid evidence that regular screening through Pap testing reduces cervical cancer mortality [9][10][11], refugee and immigrant women are least likely to be screened [12][13][14]. Foreign-born women are more than three times as likely to have never had a Pap smear, [13] and Asian immigrant women continue to have strikingly low screening rates (75.4% for Pap smears) [15] compared with the general U.S. screening rate of 84.5%.…”
Section: Introductionmentioning
confidence: 99%
“…Insurance status has been shown to be a strong predictor of screening attendance in the United States (22), where screening is mainly opportunistic. The impact of insurance status was demonstrated in a study in which higher screening attendance was observed among insured immigrants than among uninsured natives (23). However, screening attendance was also significantly lower among immigrants in countries with organized screening programs although many such programs offer screening free of charge.…”
Section: Discussionmentioning
confidence: 99%
“…Income may also be relevant in the setting of organized screening, as women in some countries have to pay user fees. It is possible that part of the difference observed could be explained by sociodemographic disparities, as adjusting for sociodemographic factors can attenuate or eliminate ethnic differences related to attendance (23,25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Legislation, such as the Illegal Immigration Reform and Immigrant Responsibility Act, the Antiterrorism and Effective Death Penalty Act and the Personal Responsibility and Work Opportunity Reconciliation Act, mandate differential access to health-related resources and services depending on U.S. citizenship status [21]. Citizenship status is known to be associated with insurance status and access to conventional care [22] and has also been analyzed in studies of other health outcomes in immigrant population [8,23,24]. Immigrant status has been shown to be protective in relation to some positive health behaviors, such as lower consumption of high-fat foods [25,26]; however, immigrant status has also perpetuated poor health care access through structural constraints such as residential segregation [26,27].…”
Section: Introductionmentioning
confidence: 99%